OPINI MAHASISWA DALAM PEMILU PRESIDEN 2019 (STUDI KASUS AKTIFIS BEM FISIP TENTANG #2019GANTIPRESIDEN PADA LIMA (5) PERGURUAN TINGGI DI KABUPATEN JEMBER) - Juariyah Juariyah; Nurul Wijayanti (Universitas Muhammadiyah Jember, 2020)
Opinion is formed through information in the mass media that causes controversy and reap the response of the community to finally be able to influence the decision in the general election. The 2019 election was a very interesting political event, because at the same time the Indonesian people elected the President and the people's representatives. The theory used in this research is the theory of opinion formation that has been developed by Noelle-Neumann, the Spiral of Silence theory. The research method uses a qualitative approach with in-depth interview techniques at ten (10) Bem activists in 5 (five) universities in Jember Regency. The results showed that the opinions that emerged from several Bem FISIP administrators in Jember District were very diverse, they channeled them through social media which was considered as the most updated media.